RUSSIAN ECONOMY FINANCIAL SECTOR ORGANIZATIONS TAXATION PERSPECTIVES - L. Kostina (Publishing House of the State University of Management, 2018)
The topical issues related to the development of taxation in the financial sector organizations of the Russian economy have marked. The author determines the main features of the functioning of the financial sector of the economy, highlighting its problems and prospects for development. Banking organizations and prospects for their taxation have considered, taking into account the current state and problems as the main institution in the financial sector of the economy. The author gives a number of recommendations, which will ensure the interaction between the banking sphere and the taxation system as a whole. In addition, the article examines the problems and prospects for taxation of insurance organizations. The same gives recommendations and directions on improving the taxation system of insurance organizations, thereby leading to stabilization of the country's economy.